Develop a framework to integrate the MATLAB GUI Apps - Florentine, Nonny (2016)
The development of the Graphical User Interfaces (GUIs) has been found to be a essential component in learning of Digital Signal Processing (DSP) topics. In this project, we will be developing a set of DSP software learning tool in the form of GUI by using the MATLAB GUIDE. These software learning tool is called the MATLAB GUI apps. Initially our aim was to develop a framework of the application called the GUIDE Educational Tool (GET) app to integrate these MATLAB GUI apps such that when the user runs the main code, the system will detect all the available MATLAB GUI apps. However this framework was initially acceptable until which the idea of integrating other courses came about. ‘What if the user wants to add new MATLAB GUI apps from other courses?’. The answer is we need a one-stop platform that can facilitate the various MATLAB GUI apps from the different courses available. Also to make this set of learning tool more versatile, we want the next user to be able to add new MATLAB GUI apps without ever changing the main code. The structure of the one-stop platform was implemented by using an XML-based architecture. This report will include the implementation of the framework and describing the features of the DSP MATLAB GUI apps that have been developed. At the end of this project, a total of 8 DPS MATLAB GUI apps were developed. Finally, to make sure that the functionality of the system is working we created a new course called the ‘Digital Communications’. This course will be the example for a user on how to create new MATLAB GUI apps. Two MATLAB GUI apps were developed under this course.